2022
DOI: 10.1093/eurpub/ckac062
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Activity Environment Policy Index for monitoring government policies and actions to improve physical activity

Abstract: Background A multifaceted response, including government action, is essential to improve population levels of physical activity (PA). This article describes the development process of the ‘Physical Activity Environment Policy Index’ (PA-EPI) monitoring framework, a tool to assess government policies and actions for creating a healthy PA environment. Methods An iterative process was undertaken. This involved a review of policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…23 Prioritizing education policies (over, e.g., changes in urban design and broadening cycling paths) may be related to policymakers' perceptions that such policies are easier to implement and thus are more feasible. 26 Adolescents' focus on structural policies in our study might be influenced by the procedures of our study. Photovoice was preceded by Youth Alliance meetings where young people were asked to discuss policies that help "everyone" in their community, which could sensitize adolescents to actions that affect those people who have less resources (e.g., time) or limited capabilities (e.g., learning skills) and thus are less likely to enroll in extracurricular education programs (or other agentic policies, requiring their own resources and effort).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Prioritizing education policies (over, e.g., changes in urban design and broadening cycling paths) may be related to policymakers' perceptions that such policies are easier to implement and thus are more feasible. 26 Adolescents' focus on structural policies in our study might be influenced by the procedures of our study. Photovoice was preceded by Youth Alliance meetings where young people were asked to discuss policies that help "everyone" in their community, which could sensitize adolescents to actions that affect those people who have less resources (e.g., time) or limited capabilities (e.g., learning skills) and thus are less likely to enroll in extracurricular education programs (or other agentic policies, requiring their own resources and effort).…”
Section: Discussionmentioning
confidence: 99%
“…25 Another recent study using a different PA framework and conducted by means of interviews with European policymakers and researchers from the field of PA policies indicated that the most important policy domains refer to transport and urban design (both refer mostly to structural policies) as well as PA education policies. 26 Besides similarities that indicate that the critical awareness of youth is shared by other stakeholders involved, youth clearly prioritize structural policies that may have the highest potential to reduce health inequalities. 23 Prioritizing education policies (over, e.g., changes in urban design and broadening cycling paths) may be related to policymakers' perceptions that such policies are easier to implement and thus are more feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bellew and colleagues (20) identify multidisciplinary action and consultation as necessities in successful PA related policy. However, ensuring strong monitoring mechanisms are embedded in PA policy is of utmost importance to the overall effectiveness of a policy (34,35). There were very few examples of effective evaluation and monitoring mechanisms in local and national walking policies identified in the current content analysis.…”
Section: Irish Walking Policy-synergies and Specificitiesmentioning
confidence: 96%
“… 16 An unhealthy physical activity environment may be caused by a lack of ‘upstream’ policy progress in domains known to have a positive impact on physical activity behaviour, and when combined with a lack of effective infrastructure support for policy implementation, then the inactivity pandemic is likely to sustain, as the ‘system’ or environment remains unchanged despite best ‘downstream’ or programmatic efforts. 17 …”
Section: Public Policies With Potential Influence On Food and Physica...mentioning
confidence: 99%